Analisis Kinerja Frame Relay Pada Cloud Router dan PC Berbantuan Cisco Packet Tracer Student - Fadel Montoya; Enjel Rosiana; Ilham Firdaus; Didik Aribowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Data networks are the lifeblood of modern life, connecting people and information at high speeds. Frame Relay technology plays an important role in delivering efficient and reliable data connectivity, like a water pipe that flows information seamlessly. Specifically designed for Wide Area Network (WAN), Frame Relay works at layer 2, optimizing data transmission between remote locations. This research uses experimental research. Experimental research is a manipulative process that needs to be carried out by applying certain treatments/treatments to research subjects and observing/measuring the effects. This research was conducted by looking at the results of the ping test on Router 1, Router 2 and Router 3 in sending messages over the network in 1 cloud The